IMPLEMENTASI STANDAR PEMERIKSAAN KEUANGAN NEGARA (SPKN) 2017 DALAM PELAKSANAAN PEMERIKSAAN KEUANGAN OLEH BADAN PEMERIKSA KEUANGAN REPUBLIK INDONESIA - Tumija Tumija; M. Ade Febriansyah (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2019)
The aim of this research is to find the mechanism of financial audit conducted by the Supreme Audit Board of the Republic of Indonesia after the SPKN 2017 update, what improvements and new things contained in the SPKN 2017, as well as any obstacles that arise in the implementation of SPKN 2017. This research uses descriptive method with an inductive approach that describes the field situation and analysis . Data collection techniques are interview, observation and documentation then analyzed by doing data reduction, data presentation and data verification. The result of the research shows that there is a change of audit mechanism conducted by the Indonesian Supreme Audit Institutioncaused by the change of the standard regulation system of audit from the previous based on the detail rules into the standard with the rule based principle. Keywords: Indonesian Supreme Audit Institution, SPKN, Implementation